Overcoming Banking Limitations: the Use of Alternative Finance - Guercio, María Belén (2024)
The article explores the relationship between bank credit constraints and the utilization of alternative financing for a sample of Latin American SMEs (Small and Medium Enterprises). It analyzes whether the limitation of firms to obtain bank credit affects the likelihood of turning to other forms of financing, such as informal loans, personal loans, or trade credit. Logistic regression models are estimated to test whether companies facing bank credit constraints can access alternative forms of financing. The results reveal that the probability of resorting to alternative financing increases if companies are excluded from bank financing.